Analysis of a Possible Coupling in a Thrust Inverter - Lardat, Raphael; Koobus, Bruno; Schall, Eric; Dervieu, Alain; Farhat, Charbel (European Journal of Computational Mechanics, 2000)
We present the study of the interaction between the flow in a thrust inverter and a flap playing a central role in the flow deviation. The flow is limited by a rather closed vessel and presents acoustic modes which can be amplified by recirculations. Such modes may interfere with structural modes. The analysis is conducted with a fully ALE 3D approach involving a nonlinear compressible flow solver, coupled with a shell finite element model.